Les enfants d’abord ? La prise en charge médico-légale des mineurs entre soin et expertise - Romain Juston (Anthropologie & Santé)
Forensic examinations on minors are a borderline case of forensic expertise because they destabilise the care/record dichotomy according to which therapeutic work must disappear behind the expertise of assaulted bodies. This paediatric expertise brings to the forefront a defining debate in forensic medicine around the choice of those having mandate to carry out acts on judicial requisitions. Paediatricians consider that they should have a voice when the handling of children requires care and screening. Claiming a paediatric prism, forensic paediatricians accuse the requisitions of limiting forensic operations to simple acts of constat, while their expertise is also that of paediatric specialists of children. By placing "children first", they intend to deal with specifically paediatric problems without reducing the examinations of minors to the level of expertise alone. Based on an ethnographic survey of these professionals, the article shows that paediatric specialty training has a strong impact on the practice of forensic expertise of minors, constraining forensic work between a requirement for evidence and a therapeutic concern.